2021
DOI: 10.3390/w13152121
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Macroinvertebrate Responses to Water Abstraction in Alpine Streams

Abstract: Exploitation of hydropower potential in alpine areas undermines the ecological integrity of rivers. Damming and water abstraction substantially alter the physical habitat template of rivers, with strong repercussions on aquatic communities and their resources. Tools are needed to predict and manage the consequences of these alterations on the structure and functioning of macroinvertebrate communities and resource availability in alpine streams. We developed habitat preference models for taxa, functional feedin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 67 publications
1
8
0
Order By: Relevance
“…tot), three Diptera (Diamesinae, Liponeura spp., and Simuliidae), two Plecoptera of Protonemura genus, and two Trichoptera of Rhyacophila genus. These results support the study by Consoli et al (2021) who showed higher abundances of Baetis alpinus , Protonemura spp., Rhyacophila spp., and Simuliidae at high shear stress, and Snook and Milner (2002) who showed that temporarily attached macroinvertebrates (such as Simuliidae) persisted in high shear stress conditions. Consequently, stream flow reduction due to both water abstraction and glacier retreat (Milner et al, 2009) will, by reducing velocities and water depths in microhabitats (Dewson et al, 2007), undoubtedly impact these rheophilic taxa (Cauvy‐Fraunié et al, 2016).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…tot), three Diptera (Diamesinae, Liponeura spp., and Simuliidae), two Plecoptera of Protonemura genus, and two Trichoptera of Rhyacophila genus. These results support the study by Consoli et al (2021) who showed higher abundances of Baetis alpinus , Protonemura spp., Rhyacophila spp., and Simuliidae at high shear stress, and Snook and Milner (2002) who showed that temporarily attached macroinvertebrates (such as Simuliidae) persisted in high shear stress conditions. Consequently, stream flow reduction due to both water abstraction and glacier retreat (Milner et al, 2009) will, by reducing velocities and water depths in microhabitats (Dewson et al, 2007), undoubtedly impact these rheophilic taxa (Cauvy‐Fraunié et al, 2016).…”
Section: Discussionsupporting
confidence: 93%
“…On the contrary, flow reduction in alpine streams could favour six limnophilic taxa that preferred lower shear stress, such as Limnephilinae and Ecdyonurus spp. tot (Consoli et al, 2021; Dolédec et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations